Dostoevsky and the religious experience. An analysis of The Possessed - Sara García Sanz; Chinwe Nzewi (Church, Communication and Culture, 2017)
This paper is a theological approach to the religious world of Dostoevsky. One of the most important themes for theology in the twentieth century – and indeed at all times – is the connection between anthropology and theology. In the past, this connection was formulated from the perspective of metaphysics and ethics, using knowledge as a guiding principle. In Dostoevsky, the thread that connects the anthropological with the theological is the religious dimension, which is not limited simply to man the creature’s relationship with God the Creator, but involves the totality of existence. We will present the great models of religious existence that appear in Dostoevsky's work and his vision of paganism, focusing on the analysis of The Possessed. It is a theological re-reading of Dostoevsky from the prism of the relationship between religion and revelation, using elements of the phenomenology of religion. Dostoevsky's perspective is particularly related to contemporary theology, because it emphasizes the experiential-existential dimension of religion, and highlights the impossibility of a supposedly areligious Christian existence.